TAXPAYER COMPLIANCE IN TAX FILING AT PALEMBANG CITY - - Marthadinasyah; Inten Meutia; - Mukhtaruddin; Dewa Saputra (InFestasi, 2014)
This study is aimed to analyse factors that influence tax payers' compliance intention to file annual income tax returns. Theory of planned behaviour (Ajzen, 1991) is used as theoretical framework to develop hypothesis that tax payers' compliance intention in filing annual income tax returns is influenced by attitude to comply, subjective norms, perceived behavioural control and moral. This study used 181 individual tax payers registered in Small Tax Office (STO) Palembang Ilir Timur, as respondent whom completed specifically-developed questionnaire that measured each of the four independent variable as well as their compliance intention to file their annual income tax returns. A structural equation model analysis of their responses found that perceived behavioural control and moral positively influence the compliance intention of taxpayers in filing annual income tax returns. Nevertheless, attitude to comply and subjective norms have no significant statistical effect.